Implications of immunosuppressive agents in cardiovascular risks and carotid intima media thickness among lupus nephritis patients - Sazliyana, S; Shahrir, MSM; Kong, CTN; Tan, HJ; Hamidon, BB; Azmi, MT (Sage Publications Ltd, 2024)
Introduction: Patients with systemic lupus erythematosus, particularly with lupus nephritis (LN), are at risk of premature cardiovascular (CV) disease. Objective: To determine the association between immunosuppressive medications, traditional CV risk factors and carotid intima media thickness (CIMT) among patients with LN. Methodology: This was a cross-sectional study in which consecutive LN patients attending the Nephrology/SLE Clinic were evaluated for traditional CV risk factors. Detailed information on their treatment was obtained from their medical records. CIMT, an excellent marker of subclinical atherosclerosis, was measured by B Mode carotid ultrasound. Results: A total of 82 patients with LN with a mean age of 33.9 +/- 9.8 years were recruited. More than half had hypertension (n = 55, 67.1%) and dyslipidemia (n = 43, 52.4%) as traditional CV risks. Longer history and higher cumulative dose of corticosteroids were associated with hypertension, but use of intravenous methylprednisolone was associated with lower systolic and diastolic blood pressure and lower serum total cholesterol and triglyceride levels (p < 0.05 each). Hydroxychloroquine use was associated with lower total serum cholesterol and serum low-density lipoprotein levels (p < 0.05). Although the use of cyclosporine A (CyA) was associated with hypertension (p < 0.05), those who received a lower cumulative dose of CyA had thicker CIMT (r(s) = -0.33, p = 0.01) and CyA use remained an independent predictor of CIMT during linear regression analysis. There were no associations between CIMT and cumulative dose and duration of steroids, hydroxychloroquine, azathioprine, mycophenolic acid and cyclophosphamide. Conclusion: Aggressive treatment of severe LN and the use of CyA as a steroid-sparing agent may have protective effects against premature atherosclerosis. Lupus (2011) 20, 1260-1266.